A Study To Determine The Level of Presentation of Local Dishes in Finne-Dining Restaurants - Sarıoğlan, Mehmet; Deveci, Bilal; Özata, Esat; Gelen, Özlem (Academician Publishing Book DOI Portal, 2024)
-